Berberine ameliorates chronic kidney disease through inhibiting the production of gut-derived uremic toxins in the gut microbiota - Libin Pan; Hang Yu; Jie Fu; Jiachun Hu; Hui Xu; Zhengwei Zhang; Mengmeng Bu; Xinyu Yang; Haojian Zhang; Jinyue Lu; Jiandong Jiang; Yan Wang (Elsevier, 2023)
At present, clinical interventions for chronic kidney disease are very limited, and most patients rely on dialysis to sustain their lives for a long time. However, studies on the gut-kidney axis have shown that the gut microbiota is a potentially effective target for correcting or controlling chronic kidney disease. This study showed that berberine, a natural drug with low oral availability, significantly ameliorated chronic kidney disease by altering the composition of the gut microbiota and inhibiting the production of gut-derived uremic toxins, including p-cresol. Furthermore, berberine reduced the content of p-cresol sulfate in plasma mainly by lowering the abundance of g_Clostridium_sensu_stricto_1 and inhibiting the tyrosine-p-cresol pathway of the intestinal flora. Meanwhile, berberine increased the butyric acid producing bacteria and the butyric acid content in feces, while decreased the renal toxic trimethylamine N-oxide. These findings suggest that berberine may be a therapeutic drug with significant potential to ameliorate chronic kidney disease through the gut-kidney axis.